Complete genome sequence of local Malaysian Fowl adenovirus serotype 8b UPM T221 strain - Azli, Bahiyah; Salim, Nur Farhana; Hair-Bejo, Mohd; Sohaimi, Norfitriah Mohamed; Hamid, Nor Asilah Wati Abdul; Isa, Nurulfiza Mat (University of Malaya, 2024)
Recently, Fowl adenovirus serotype 8b (FAdV-8b) infection has emerged as a serious threat to Malaysia’s poultry industry, acting as a causal agent of Inclusion Body Hepatitis (IBH) with a mortality rate of 10-30% among chickens. In this study, we isolated an FAdV strain from the liver of an IBHpositive dead commercial broiler chicken in Tawau, Sabah, and subjected it to pathogenicity analysis and Whole genome sequencing (WGS). Upon inoculation of UPM T221 isolate into Specific pathogen-free chicken embryonated eggs, slow mortality pattern of 6- to 12-days post-infection (dpi) was recorded, with nil gross lesions of both chorioallantoic membrane (CAM) and liver observed during harvesting. Upon subjection to WGS, the genome of UPM T221 was found to be 44722 bp in length with 58.1% GC content, 37 coding sequence (CDS), identifying the isolate as a strain from FAdV-8b of the FAdV-E. Interestingly, the left ORF regions and central genes showed a higher potential for significant genetic divergence with Single nucleotide polymorphism (SNPs) and InDels gaps. These variants are displayed in the within the structural capsid of UPM T221, such as hexon and penton, as well as in virion replication processes such as DNA polymerase and pTP. These findings of less virulence, non-pathogenic UPM T221 profile proposed the strain as a suitable live attenuated candidate vaccine, also contributing to the current understanding of the genetic diversity of FAdV for developing autogenous vaccines or diagnostic materials especially against local strain infections.